2023
DOI: 10.1111/fwb.14045
|View full text |Cite
|
Sign up to set email alerts
|

High temperature events shape the broadscale distribution of juvenile Atlantic salmon (Salmo salar)

Abstract: Summer water temperatures within many temperate rivers regularly surpass the incipient lethal temperature for juvenile Atlantic salmon (c. 27°C), causing widescale abandonment of territory in favour of areas of cooler water (thermal refuges). This study aims to highlight the influence of thermal refuges on river‐scale abundance patterns. That is, do salmon parr adjust their distribution over time according to proximity to thermal refuges? Twelve reaches (seven reference: five refuge) were chosen along a 17‐km … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…We also found evidence that less variable and cooler temperature regimes in the nearby main stem river led to higher estimated trout abundances within thermal refuges, highlighting the complex roles that main stem rivers play in determining refuge use (e.g., Brewitt et al, 2017;Corey et al, 2023). Railsback and Harvey (2023) expanded on this, implying that any thermal refuge and nearby river characteristics providing opportunities for food intake, lower energy costs, or reduced predation risks are also important.…”
Section: Model Process and Parametermentioning
confidence: 69%
See 2 more Smart Citations
“…We also found evidence that less variable and cooler temperature regimes in the nearby main stem river led to higher estimated trout abundances within thermal refuges, highlighting the complex roles that main stem rivers play in determining refuge use (e.g., Brewitt et al, 2017;Corey et al, 2023). Railsback and Harvey (2023) expanded on this, implying that any thermal refuge and nearby river characteristics providing opportunities for food intake, lower energy costs, or reduced predation risks are also important.…”
Section: Model Process and Parametermentioning
confidence: 69%
“…We estimated a maximum of 118.86 (95% CRI = 1.27–815.93) trout within the Furnace Brook refuge and 2.272 trout m −2 within the Pine Swamp Brook thermal refuge across all surveys. Fish abundance within thermal refuges may vary with population abundance within the nearby main stem river, the availability of thermal refuges throughout the river segment, and main stem river temperatures (e.g., Corey et al, 2023; Ebersole et al, 2001; Railsback & Harvey, 2023), making direct comparisons across studies difficult. Still, our estimates of trout density within thermal refuges were similar to estimates reported in other riverscapes (Brewitt et al, 2017; Morgan & O'Sullivan, 2023; Wang et al, 2020; Wilbur et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corey et al [62] observed that a very high proportion (96-100%) of juvenile Atlantic salmon remained in their original tagging reaches post-thermal events if they contained thermal refuges, but a lower proportion (62%) returned to a reach where no cold-water refuges were located. This finding led Corey et al [120] to investigate the long-term effects of cold-water refuge availability on the relative abundance of juvenile Atlantic salmon along a 17-km segment of river and they found that while the relative abundance increased in the reaches with thermal refuges in summer, an equilibrium in the abundance was regained later in autumn when subsequent thermal events became unlikely. In the same study, Corey et al [120] revealed that the tributary confluence thermal refuges with the highest temperature difference from the main river had the highest effect on the relative abundance of Atlantic salmon across five thermal refuges during the summer season.…”
Section: Behaviour In the Refuges And Post-aggregation Movementsmentioning
confidence: 99%
“…This finding led Corey et al [120] to investigate the long-term effects of cold-water refuge availability on the relative abundance of juvenile Atlantic salmon along a 17-km segment of river and they found that while the relative abundance increased in the reaches with thermal refuges in summer, an equilibrium in the abundance was regained later in autumn when subsequent thermal events became unlikely. In the same study, Corey et al [120] revealed that the tributary confluence thermal refuges with the highest temperature difference from the main river had the highest effect on the relative abundance of Atlantic salmon across five thermal refuges during the summer season. Similar observations regarding a preference towards a larger temperature differential between the mainstem and tributary has also been seen for juvenile rainbow (steelhead) trout [100].…”
Section: Behaviour In the Refuges And Post-aggregation Movementsmentioning
confidence: 99%